Glaucoma and dry eye disease: the role of preservatives in glaucoma medications (Faculty of Medicine Universitas Indonesia, 2011)
Glaucoma is a common cause of irreversible blindness with increasing prevalence. Some of glaucoma patients will also experience dry eye. Dry eye is the most frequent side effect related to benzalkonium chloride (BAC)-containing eye drop used for glaucoma patients. In addition, glaucoma and dry eyes have shared risk factors that are old age and female. Dry eye among glaucoma patients need to be treated promptly as it produces discomfort, reduces patients' compliance and decreases success rate of glaucoma therapy. Dry eye symptoms can be treated by applying preservative-free eye drop, giving combination of preservative containing and preservative-free eye drop to reduce BAC exposure, prescribing artificial tear and conducting surgery to minimize or eliminate the need of topical medication. (Med J Indones 2011; 20:302-5) Keywords: benzalkonium chloride, dry eye, glaucoma